2013
DOI: 10.1073/pnas.1318431110
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailable copper modulates oxidative phosphorylation and growth of tumors

Abstract: Significance This paper describes the mechanism by which copper mediates the interplay between the two energy-producing pathways, respiration and glycolysis. Many tumors produce increased levels of lactate, even when oxygen abounds, reflecting aerobic glycolysis (“Warburg effect”), whereas most normal tissues solely use respiration. We demonstrate that reducing systemic copper with a chelating drug impaired mitochondrial energy metabolism and decreased ATP levels despite induction of glycolysis. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
257
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(286 citation statements)
references
References 46 publications
10
257
0
1
Order By: Relevance
“…In this study, we demonstrate that glutathione inhibits ERK phosphorylation through copper chelation, which is phenocopied by two other copper chelators, tetrathiomolybdate and trientine. Copper has been considered as a target for cancer therapy (42), but our results suggest it may not be a good target because copper chelators may enrich for cancer stem cells, whereas copper ionophores will increase cancer cell proliferation (43), neither of which is desired. The inhibition of ERK phosphorylation by glutathione is consistent with the effect of ATN-224, a specific copper chelator that is under clinical trials, which also inhibits ERK phosphorylation (44).…”
Section: Discussionmentioning
confidence: 85%
“…In this study, we demonstrate that glutathione inhibits ERK phosphorylation through copper chelation, which is phenocopied by two other copper chelators, tetrathiomolybdate and trientine. Copper has been considered as a target for cancer therapy (42), but our results suggest it may not be a good target because copper chelators may enrich for cancer stem cells, whereas copper ionophores will increase cancer cell proliferation (43), neither of which is desired. The inhibition of ERK phosphorylation by glutathione is consistent with the effect of ATN-224, a specific copper chelator that is under clinical trials, which also inhibits ERK phosphorylation (44).…”
Section: Discussionmentioning
confidence: 85%
“…metal homeostasis | molecular imaging | luciferin | metabolic liver disease | copper C opper is an essential mineral for all higher organisms, serving as a redox-active cofactor for physiological processes, including respiration (1,2), antioxidant defense (3,4), neurotransmitter synthesis and metabolism (5), epigenetic modifications (6), and emerging roles in dynamic signaling networks (7)(8)(9)(10)(11). This same redox activity also poses a potential danger, requiring highly orchestrated regulation of copper pools to prevent oxidative stress and free radical damage events that are detrimental to health (12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Copper levels in tumors affect cytochrome c oxidase activity, additional bioavailable copper facilitates increased production of ATP, which is consumed to fuel rapid proliferation of cancer cells. Thus, copper may not initiate transformation, but may stimulate proliferation of transformed cells by providing energy needed for cell-cycle progression as proposed Ishida and coworkers [42]. Additionally, copper ions are well suited to facilitate formation of ROS that can damage biomolecules, including DNA and chromatin.…”
Section: Metals and Its Relationship With Cancermentioning
confidence: 98%
“…Some studies have shown that serum copper levels are elevated in cancer patients and correlate with the severity of the disease and the response to therapies [42,43]. Copper-chelating drugs have been reported to have antiangiogenic activity in animal models.…”
Section: Metals and Its Relationship With Cancermentioning
confidence: 99%